Evaluating the safety and efficacy of SILS and SILS+1 port laparoscopic surgery for colorectal resection: a systematic review with meta-analysis and trial sequential analysis of RCTs - Lu, Kai; Shu, Shilong; Zhong, Furui; Yang, Hua; Cheng, Yong; Zhang, Faqiang (Frontiers in Oncology, 2025)
BackgroundAs minimally invasive techniques evolve, reduced-port laparoscopic colorectal resection, including single-incision (SILS) and single-incision plus one (SILS+1) approaches, has gained increasing clinical traction. However, whether it offers definitive advantages over conventional multiport laparoscopic surgery remains contentious. This meta-analysis aimed to comprehensively evaluate the safety and efficacy of reduced-port laparoscopic surgery (RLS) for colorectal resection and validate the robustness of findings through trial sequential analysis (TSA).MethodsA systematic literature search was conducted across Web of Science, PubMed, Cochrane Library, and Embase from database inception to March 21, 2025, to identify RCTs comparing RLS with conventional laparoscopic surgery (CLS) for colorectal resection. Methodological quality was assessed using the Cochrane Risk of Bias Tool. Meta-analyses were performed in RevMan 5.3, with TSA employed to control for random errors. Primary endpoints included operative time, intraoperative blood loss, intraoperative complications, postoperative complications, and postoperative pain.ResultsFourteen RCTs involving 1,713 patients were analyzed. Pooled data demonstrated no statistically significant differences between RLS and CLS in operative time (SMD: 0.29; 95% CI: −0.07 to 0.64; p = 0.11), intraoperative blood loss (SMD: 0.04; 95% CI: −0.06 to 0.15; p = 0.40), intraoperative complications (OR: 1.6; 95% CI: 0.88 to 2.88; p = 0.12), or postoperative complications (OR: 0.88; 95% CI: 0.67 to 1.17; p = 0.38). RLS was associated with significantly shorter incision length (SMD: −1.60; 95% CI: −2.37 to −0.83; p < 0.0001). Secondary outcomes, including complication severity, resection margins, lymph node harvest, time to first flatus, hospital stay, conversion rates, and anastomotic leakage, showed comparable results between approaches.ConclusionRLS demonstrates comparable safety profiles and operative efficiency to conventional laparoscopic resection, and with its principal advantage being reduced incision length, this approach can serve as an alternative surgical option for patients.